The Role of Perceived Organizational Support on Employee Turnover Intention - Nadia Khairina (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2022)
Based on data obtained in 2016, it is known that at PT. X, the number of employees who made a turnover or changed jobs was 40 people or the equivalent of 25% of the total 135 employees at PT. X. Employees who have a high level of perception of organizational support will show high commitment and will not look for alternative jobs or have the desire to move out. As a result of previous research, perceived organizational support is one factor that reduces turnover intensity. This study recruited participants using a purposive sampling technique in which 55 men agreed to be participants. The analysis showcases a negative relationship between perceived organizational support and turnover intensity. The higher the perceived level of organizational support, the lower the turnover intensity behavior. Another finding is there is a 12.5% effect of perceived organizational support on turnover intention, which means that perceived organizational support is one of the main factors that directly affect turnover intention. This finding can be another evidence that perceived organizational support significantly affects turnover intention.